PENINGKATAN KESADARAN NILAI PANCASILA MELALUI PROYEK POHON KEBAIKAN DI SD NEGERI GELARAN 1 KARANGMOJO - Nina Kumalasari; Devinda; Siti Maisaroh (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2026)
This study aims to enhance students’ understanding of the values of Pancasila among third-grade students at SD Negeri Gelaran I Karangmojo by implementing a Project-Based Learning (PjBL) model supported by the “Tree of Goodness” media. The background of this study is the low level of student awareness in applying the values of Pancasila, such as a sense of responsibility, cooperation, tolerance, discipline, and social concern in their daily lives. The method used was Classroom Action Research (CAR) with the Kemmis and McTaggart approach, which includes the stages of planning, implementation, observation, and reflection. This study was conducted in two cycles with 31 students participating. The results showed an increase in awareness of Pancasila values, marked by a rise in the average score from 74.52 in Cycle I to 84.19 in Cycle II. The percentage of students meeting the standard also increased from 61.29% to 77.42%. Thus, the Project-Based Learning model supported by the Tree of Virtue can be relied upon as an effective learning method to enhance awareness of Pancasila values among students